Importance of Ventricular Tachycardia Induction and Mapping for Patients Referred for Epicardial Ablation. Issue 11 (2nd September 2015) - NAZER, BABAK; WOODS, CHRISTOPHER; DEWLAND, THOMAS; MOYERS, BRIAN; BADHWAR, NITISH; GERSTENFELD, EDWARD P.
<x xml:space="preserve">Abstract</x> Background Many nonischemic cardiomyopathy (NICMP) patients referred for catheter ablation of ventricular tachycardia (VT) undergo an initial epicardial approach under general anesthesia (GA). However, GA may suppress inducibility and decrease tolerance of induced VT, leaving substrate modification as the sole ablation method. Objectives Determine the utility of a strategy of initial programmed electrical stimulation (PES) under light sedation in patients referred for epicardial ablation of VT. Methods Of 68 NICMP patients referred for VT ablation, 25 were referred specifically for epicardial ablation. All patients underwent PES under conscious sedation, with conversion to GA and epicardial access only if VT morphology and/or endocardial mapping suggested an epicardial substrate. Results VT was induced with PES in 24 of 25 patients (mean age 52 years; 76% male; ejection fraction 38 ± 18%). VT was hemodynamically tolerated in 63% and unstable in 38% of patients. The noninducible/unstable VT patients underwent substrate modification based on voltage and pace mapping. Of the patients with stable VT, 73% were mapped and ablated endocardially (six right ventricle, three left ventricle, one left coronary cusp, one middle cardiac vein), and 33% were successfully ablated in areas of normal endocardial voltage. After ablation, the clinical VT was noninducible in all patients. After mean follow‐up of 10 months, 80% were free of implantable cardioverter defibrillator shocks or sustained VT. Conclusions An initial approach of PES and entrainment mapping under conscious sedation is critically important for patients with NICMP referred for epicardial ablation. Empiric ablation of endocardial/epicardial scar would have missed the clinical VT in 20% of patients.